Relational integration/assimilation? A critical dialog with postcolonial and mainstream perspectives - Ivan Polynin (Frontiers in Political Science)
Mainstream studies on integration and assimilation, epitomized by scholars like Richard Alba and Nancy Foner, tend to equate the terms, describing them as processes in which migrants lose their ethnic salience and gradually become barely distinguishable from the white majority. Postcolonial critiques, most notably from Willem Schinkel and Adrian Favell, challenge these views labeling them as methodological nationalism that allegedly perpetuates racial biases and reduces migrants’ agency. Ultimately Schinkel calls for deconstruction of the entire field of migration studies, while Favell advocates for separating integration from the logic of nation state. To rebuild a once-failed dialog between these influential but divergent perspectives, this article utilizes Klarenbeek’s relational integration theory, which argues in favor of balancing egalitarian social relations between majorities and minorities over one-directional integration models that assign migrants the role of passive recipients. Using Klarenbeek’s framework, I offer a critical perspective on both the mainstream tendency to problematize migrants and the radical deconstruction of integration suggested by postcolonial theorists. I argue that both mainstream and postcolonial scholars should move away from methodological whiteness, acknowledge the conceptual distinction between assimilation and integration, and incorporate insights from acculturation theories to foster a much-needed egalitarian dialog between their competing approaches.